Entry Dynamics, Capacity Utilisation and Productivity in a Dynamic Open Economy - Marta Aloi; Huw D. Dixon (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper analyses an open economy Ramsey model with an endogenous labour supply without capital. The technology defines an optimal firm size. Changes to the number of firms is subject to adjustment costs, so that the entry dynamics is determined endogenously. We find that there is a short run transitory productivity dynamic introduced when there is imperfect competition due to changes in capacity utilization. We are able to analyze this in different contexts, including demand and technology shocks, both anticipated and unanticipated.
Keywords: 330; entry; capacity utilisation; adjustment costs; Ramsey